2015
DOI: 10.1002/app.42877
|View full text |Cite
|
Sign up to set email alerts
|

PET interleaving veils for improved fracture toughness of glass fibre/low‐styrene‐emission unsaturated polyester resin composites

Abstract: The use of interleaved polyethylene terephthalate (PET) veils to increase the interlaminar fracture toughness of glass fiber-reinforced, low-styrene emission, unsaturated polyester resin composites, was investigated. PET, being chemically similar to the unsaturated polyester resin, was expected to exhibit good wetting and strong interaction with the matrix. Composite laminates were manufactured by hand lay-up, with the veil content varying up to 7%. The effects of PET veils on the interlaminar shear strength, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…They showed that PET veils had no significant effect on the IFT of composites while PA veils increased the mode I interlaminar fracture toughness values at crack initiation and propagation levels improved by 59 and 90%, respectively. Fitzmaurice et al [19] also showed that PET veils were not effective for improving Mode-I interlaminar fracture toughness of the glass fiber/ polyester resin (GF/ PE) composites due to the weaker glass/resin interface providing an alternative crack propagation path. They also showed that the incorporation of PET veils had positive effects on the flexural strength, interlaminar shear strength and damping properties of the composites.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They showed that PET veils had no significant effect on the IFT of composites while PA veils increased the mode I interlaminar fracture toughness values at crack initiation and propagation levels improved by 59 and 90%, respectively. Fitzmaurice et al [19] also showed that PET veils were not effective for improving Mode-I interlaminar fracture toughness of the glass fiber/ polyester resin (GF/ PE) composites due to the weaker glass/resin interface providing an alternative crack propagation path. They also showed that the incorporation of PET veils had positive effects on the flexural strength, interlaminar shear strength and damping properties of the composites.…”
Section: Introductionmentioning
confidence: 99%
“…Miller et al [22] observed a 40% increase in G IC with the addition of polyurethane (PU) veil. In all of these studies [18][19][20][21][22], the researchers investigated the effects of microfiber nonwoven veils on the fracture toughness of fiber reinforced composites, while other researchers went further and investigated the effects of electrospun nanofiber nonwoven veils on the delamination resistance of these composites. Although different types of nanofiber veils such as polyacrylonitrile (PAN) [23], polycaprolactone (PCL) [24] and polysulfone (PSF) [25] were studied in the literature, the majority of studies have focused on electrospun PA 66 nonwoven veils due to their high melting temperature (260°C), good compatibility with uncured resin and good mechanical properties [26].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, in another study conducted on GF/polyester composites, no significant effect on mode I ILFT was observed by PET interleave veils. 157 However, other mechanical properties such as flexural strength, ILSS, and damping resulted in improved values. Other microfiber veils of PU 134 and PA6,6 158 have exhibited positive increments in ILFT properties.…”
Section: Effects Of Interleaving On Various Properties Of Fiber-reinf...mentioning
confidence: 99%
“…Unsaturated polyester resin (UPR) is widely used in the chemical industry, construction, transportation, electronics, and other fields because of its lightweight, high strength, corrosion resistance, and simple processing technology 1–5 . Due to the low toughness, poor thermal stability, and poor aging resistance of UPR, UPR usually needs to be modified for better comprehensive properties 6–9 . The most common method is to add functional fillers in UPR, such as nanoparticles, 10–12 fibers, 13–16 elastomer, 17,18 and vegetable oil 19–21 .…”
Section: Introductionmentioning
confidence: 99%